2018
DOI: 10.1177/2047487318770299
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral arterial disease: Changes in clinical outcomes and therapeutic strategies in two cohorts, from 2002 to 2008 and from 2008 to 2014. A population-based study

Abstract: Background The aim of our study was to evaluate whether treatments for peripheral artery disease changed in two different cohorts identified in 2002 and 2008, and whether this had an impact on mortality and major clinical outcomes after six years of follow-up. Methods Using administrative health databases of the largest region in Northern Italy, we identified patients admitted to hospital for peripheral artery disease in 2002 and 2008. Both cohorts were followed for six years. All cause death, acute coronary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…NR NR Arinze et al (2018) [ 61 ] OptumLabs Data Warehouse from 2004 to 2014 AMI, stroke AMI: 410; stroke: 434, 434.0, 434.00, 434.01, 434.1, 434.10, 434.11, 434.9, 434.90, 434.91 (ICD-9). NR NR Baviera et al (2018) [ 62 ] Administrative health databases of Lombardy from 2002 to 2014 ACS, stroke, all cause death, major amputation ACS: 410.xx, 411; stroke: 430, 431, 434.xx, 436, 433.11; major amputation: 84.10, 84.13, 84.14, 84.15, 84.16, 84.17, 84.18, 84.19 (ICD-9). NR Authors state that diagnoses were retrieved from hospital discharge charts, which have been validated across all Italian hospitals for reimbursement purposes.…”
Section: Resultsmentioning
confidence: 99%
“…NR NR Arinze et al (2018) [ 61 ] OptumLabs Data Warehouse from 2004 to 2014 AMI, stroke AMI: 410; stroke: 434, 434.0, 434.00, 434.01, 434.1, 434.10, 434.11, 434.9, 434.90, 434.91 (ICD-9). NR NR Baviera et al (2018) [ 62 ] Administrative health databases of Lombardy from 2002 to 2014 ACS, stroke, all cause death, major amputation ACS: 410.xx, 411; stroke: 430, 431, 434.xx, 436, 433.11; major amputation: 84.10, 84.13, 84.14, 84.15, 84.16, 84.17, 84.18, 84.19 (ICD-9). NR Authors state that diagnoses were retrieved from hospital discharge charts, which have been validated across all Italian hospitals for reimbursement purposes.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of U.S. Medicare data and the National Inpatient Sample have also noted an increase in endovascular revascularisation with a concomitant decrease in open revascularisation, [16][17][18][19] as did Australian 20 and several European studies. 23 16,[19][20][21][22][23] although some studies found stable rates. 24,26 Many studies of minor amputation rates identified a mild increase.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral artery diseases constitute ominous clinical conditions with still a high burden of mortality due to poor management. 8,9 On the other hand, the growing relevance of cost-effectiveness analysis in clinical practice has led to the publication of cost-effectiveness papers in clinical journals, also outside the borders of pharmacoeconomics journals. 10 This issue contains an Australian healthcare cost-effectiveness analysis regarding low-dose rivaroxaban in 1000 hypothetical individuals with peripheral artery disease or carotid artery disease, profiled on the COMPASS trial, using a Markov model.…”
Section: Drug Therapy Rivaroxaban and Aspirin Versus Aspirin Alone Inmentioning
confidence: 99%